Systematics and biogeography of the subantarctic Leptusa (Coleoptera: Staphylinidae: Aleocharinae: Homalotini). Issue 1 (2nd January 2019) - Orlov, Igor; Solodovnikov, Alexey; Leschen, Richard A. B.
Abstract : Leptusa atriceps and L. antarctica, flightess representatives of the nearly global genus Leptusa in the remote and widely distributed subantarctic islands, are taxonomically revised. Identity and the widely disjunct distribution of L. atriceps on Falkland, South Georgia, Marion, Crozet and Kerguelen Islands are confirmed. Leptusa antarctica is found to be a complex of five species restricted to the subantarctic islands of New Zealand. Two of these species, L. sparsepunctata and L. nesiotes are here reinstated from synonymy and two others, Leptusa insulae sp. nov. and Leptusa steeli sp. nov., are described as new to science. The monophyly of subantarctic Leptusa species united in the subgenus Halmaeusa was determined by a phylogenetic study of five exemplar homalotine genera and 17 representatives of Leptusa from South America and the Holarctic based on 76 adult morphological characters. Phylogenetic placement of Halmaeusa was not firmly established. Nanoglossa, a temperate South American subgenus of Leptusa was found as a possible sister group to Halmaeusa. The distribution of Halmaeusa species with two to four species that occur sympatrically on Campbell and Auckland Islands, and other species distributed across several remote islands, provides a framework for future biogeographic study of the subantarctic Leptusa . http://www.zoobank.org/urn:lsid:zoobank.org:act:82509B9D-4BF6-47E1-B6F7-396ED193A0FA ;http://www.zoobank.org/urn:lsid:zoobank.org:act:40A3D6FC-27FF-4070-88CA-1B519ABE760A